Retrospective Study on the Application of Enhanced Recovery After Surgery Measures to Promote Postoperative Rehabilitation in 50 Patients With Brain Tumor Undergoing Craniotomy - Feng, SongShan; Xie, Bo; Li, ZhenYan; Zhou, XiaoXi; Cheng, Quan; Liu, ZhiXiong; Tao, ZiRong; Zhang, MingYu (Frontiers in Oncology, 2021)
Objective To investigate whether enhanced recovery after surgery (ERAS) can promote rehabilitation of patients after neurosurgical craniotomy. Methods The clinical data of 100 patients with brain tumor undergoing craniotomy in the Department of Neurosurgery, Xiangya Hospital, Central South University, from January 2018 to August 2020 were collected, including 50 patients in the ERAS group and 50 patients in the control group. t-Test, Wilcoxon’s rank sum test, and chi-square analysis were used to compare the clinical characteristics, prognosis, and hospitalization time between the two groups. Results There was no significant difference in gender, age, and other general clinical data between the two groups (p > 0.05). The days of antiemetic drugs applied in the ERAS group were less than those in the control group (1.00 vs. 2.00 days, p = 0.003), and the proportion of patients requiring analgesics was lower than that of the control group (30% vs. 52%, OR = 0.41, 95% CI 0.18–0.93, p = 0.031). The time of urinary catheter removal and that of patients starting ambulation in the ERAS group were shorter than those in the control group (16.00 vs. 24.00 h, and 1.00 vs. 2.00 days, p < 0.001, respectively); and the hospital length of stay (LOS) in the ERAS group was shorter than that in the control group (Total LOS, 13.00 vs. 15.50 days; Postoperative LOS, 7.00 vs. 10.00 days, p < 0.001). By analyzing the prognosis of patients in the ERAS group and control group, we found that there was no significant difference in postoperative complications and Karnofsky Performance Status (KPS) score 1 month after operation between the two groups. Conclusion The application of ERAS in craniotomy can accelerate the postoperative recovery of patients without increasing the perioperative risk, which is worthy of wide application. However, whether the ERAS measures can reduce the postoperative complications and improve the prognosis of patients still needs more large-scale case validation and multicenter collaborative study.